ISSUES WITH THE ENFORCEMENT OF THE LAW AGAINST DRUG USERS (Study of Decision Number): 214/Pid.Sus/2024/PN.Mdn) - Melia, Roslina Tiur; Siregar, Mhd. Azhali (LPPM Univ. Ibn Khaldun Bogor, 2025)
Because it can harm the nation's values, the government views the distribution and usage of drugs as one of the major national issues. Drug offenders frequently receive punishments based on court rulings that fall short of providing a sense of justice and legal clarity. Articles 114, 112, and 127 of Law Number 35 of 2009 concerning Narcotics are among the provisions that are frequently utilized to trap offenders in drug-related crimes. As a result of the articles' multiple interpretations, drug dealers and other criminals will pretend to be victims of drug-related crimes. that this will affect the imposition of short sentences, leading to unfairness in the process of implementation. The data and facts gathered by examining court rulings pertaining to criminal penalties against drug offenders and connecting them to relevant laws and regulations constitute the normative legal nature of this research, which is a method that describes or explains a fact in a methodical manner. According to the study's findings, this appears to be far more challenging in the realm of drug law enforcement. It appears that our law enforcement is ingrained in prioritizing criminal consequences. On a local, national, and worldwide scale, extraordinary encouragement is required. Regarding the case under investigation, the judge of the Medan District Court found the defendant legally and convincingly guilty in accordance with Article 112 paragraph (1) of Law No. 35 of 2009 concerning Narcotics.